Biodegradable diblock copolymeric PEG-PCL nanoparticles: Synthesis, characterization and applications as anticancer drug delivery agents. (20th October 2020) - Behl, Akanksha; Parmar, Virinder S.; Malhotra, Shashwat; Chhillar, Anil K.
Abstract: Poly (ethylene glycol) methyl ether-block-poly (Ɛ-caprolactone) copolymers are useful biomedical materials owing to their amphiphilic nature, biodegradability, biocompatibility and also due to their semi-crystalline form having a low glass transition temperature. Due to their slow drug release profile, PEG-PCL copolymers are excellent candidates for sustained delivery applications over a period of time of more than a year. This unique property has provoked their relevance specially in the area of anticancer drug delivery applications in the form of various nanoaggregates like microspheres, nanogels, nanospheres, polymersomes, micelles, etc. A large variety of anticancer drugs/bioactives have been encapsulated in PEG-PCL copolymers for developing effective anticancer drug delivery systems and also for producing controlled drug release profiles. In recent times, PEG-PCL copolymers based nanoparticles have shown tremendous advancements as anticancer drug delivery vehicles owing to their higher drug loading capacities of the hydrophobic drugs, enhanced bioavailability, keeping away from being overpowered by way of phagocytes, decreased blasted discharge, and also in increasing the scattering time of drug within the blood stream during their systemic inoculation. These nano-formulated drug delivery systems can be used for the delivery of anticancer drugs at a specific site in a targeted approach. The developed nano-formulations possess promising potential in the treatment of cancer with improved anticancer efficacy and reduced toxicity invivo . In the current review, our main focus is to highlight the development and synthesis of different types of PEG-PCL copolymers (both conventional and greener approaches) along with the physico-chemical characterization techniques used primarily for the PEG-PCL co-polymeric systems. We have also summarized the uses of PEG-PCL co-polymeric nano formulations with various anticancer drugs as drug delivery platforms in the area of anticancer chemotherapy. Graphical abstract: In the current review we highlight the development and synthesis of PEG-PCL copolymers along with the physico-chemical characterization techniques used primarily for their characterization. Also, we showed nanoformulations of PEG-PCl copolymeric systems with anticancer drugs for anticancer applications. Image 1 Highlights: Development and synthesis of different types of PEG-PCL copolymers (both conventional and greener approaches). The physico-chemical characterization techniques used primarily for the PEG-PCL co-polymeric systems. The preparation and characterization of PEG-PCL nanoparticles through diverse methods. PEG-PCL co-polymeric nano formulations with various anticancer drugs as drug delivery platforms.